A New Approach to Jacobsthal Quaternions - Aydin, Fugen Torunbalci; Yuce, Salim (UNIV NIS, FAC SCI MATH, 2017)
The Jacobsthal quaternions defined by Szynal-Liana and Wloch [35]. In this paper, we defined some properties of Jacobsthal quaternions. Also, we investigated the relations between the Jacobsthal quaternions which connected with Jacobsthal and Jacobsthal-Lucas numbers. Furthermore, we gave the Binet formulas and Cassini identities for these quaternions.
Keywords: Jacobsthal number; Jacobsthal-Lucas number; Jacobsthal quaternion; Jacobsthal-Lucas quaternion; COMPLEX FIBONACCI NUMBERS; DUAL QUATERNIONS; POLYNOMIALS; Mathematics